Prevalence of urinary incontinence among gynecological admissions at tertiary care hospital in eastern Nepal - Regmi, MC; Uprety, D; Poonam, M (Health Renaissance, 2012)
Background: Urinary incontinence is a common medical disorder. However, in the developing countries the problem is not accepted as a major health problem. Objectives: To find out the prevalence of urinary incontinence in institutionalized gynecology patients at BPKIHS and to asses the severity of incontinence and to find out its perception as health problem. Methods: All the patients aged more than 20 years and excluding pregnancy related admissions during the study period of one year (February 2005 to February 2006) were questioned with preformed questionnaire and responses were noted. All together 630 patients participated. Results: 50.6% had incontinence. Urge incontinence was more common type (60%) than stress incontinence (40%).Most of the patients did not consider it as a health problem. Conclusion: Urinary leakage is highly prevalent and should be regarded as potential health problem. DOI: http://dx.doi.org/10.3126/hren.v10i1.6001 HREN 2012; 10(1): 16-19